Effect of direct oral anticoagulant dabigatran on early bone healing: An experimental study in rats - Ioanna Kyriakaki; Theodora Karanikola; Theodoros Lillis; Eleana Kontonasaki; Nikolaos Dabarakis (Journal of Advanced Periodontology and Implant Dentistry)
Background. Dabigatran belongs to the new generation of direct oral anticoagulants (DOACs). Its advantages are oral administration and no need for international normalized ratio (INR) monitoring. Although its use has increased, its potential side effects on bone healing and remodeling have not been fully investigated. The present study aimed to evaluate the possible effects of dabigatran on early bone healing. Methods. Sixteen male Wistar rats were divided into two groups; in group A, 20-mg/kg dabigatran dose was administered orally daily for 15 days, while group B served as a control. Two circular bone defects (d=6 mm) were created on either side of the parietal bones. Two weeks after surgery and euthanasia of the animals, tissue samples (parietal bones that contained the defects) were harvested for histological and histomorphometric analysis. Statistical analysis was performed with a significance level of α=0.5. Results. No statistically significant differences were found between the two groups regarding the regenerated bone (21.9% vs. 16.3%, P=0.172) or the percentage of bone bridging (63.3% vs. 53.5%, P=0.401). Conclusion. Dabigatran did not affect bone regeneration, suggesting that it might be a safer drug compared to older anticoagulants known to lead to bone healing delay.